2017
DOI: 10.3389/fendo.2017.00047
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin—From Local Gut Hormone to Ubiquitous Messenger

Abstract: Cholecystokinin (CCK) was discovered in 1928 in jejunal extracts as a gallbladder contraction factor. It was later shown to be member of a peptide family, which are all ligands for the CCK1 and CCK2 receptors. CCK peptides are known to be synthetized in small intestinal endocrine I-cells and cerebral neurons. But in addition, CCK is expressed in several endocrine glands (pituitary cells, thyroid C-cells, pancreatic islets, the adrenals, and the testes); in peripheral nerves; in cortical and medullary kidney ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
190
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(198 citation statements)
references
References 125 publications
6
190
0
2
Order By: Relevance
“…Brain CCK has been increasingly implicated as a key regulator in diverse aspects of behavior, including feeding, satiety, memory, nociception and anxiety. 14,44,[55][56][57][58] Thus our studies elucidating mechanisms for NLP-12 regulation of circuit function in the compact nematode nervous system may have important and broadly applicable implications for neuromodulation in more complex systems.…”
Section: Discussionmentioning
confidence: 99%
“…Brain CCK has been increasingly implicated as a key regulator in diverse aspects of behavior, including feeding, satiety, memory, nociception and anxiety. 14,44,[55][56][57][58] Thus our studies elucidating mechanisms for NLP-12 regulation of circuit function in the compact nematode nervous system may have important and broadly applicable implications for neuromodulation in more complex systems.…”
Section: Discussionmentioning
confidence: 99%
“…Cholecystokinin (CCK) is another appetite-regulated hormone that is widely distributed throughout various organs and tissues [8-10] and exists in various molecular forms (CCK-58, CCK-33, CCK-22, CCK-8, and CCK-4) [11]. However, the variation in bioactive CCKs is small in among species.…”
Section: Introductionmentioning
confidence: 99%
“…The multifunctionality of CCK suggests that it may have potential as a target in the evaluation and treatment of various diseases [18-20]. A recent study demonstrated that CCK was expressed at high concentrations in cardiac myocytes [21] despite being synthesized predominantly in the gastrointestinal tract and central nervous system [10]. These findings indicate that CCK has a variety of effects as a novel cardiovascular hormone.…”
Section: Introductionmentioning
confidence: 99%
“…The CCKR signaling pathway coordinates food intake by controlling visceral functions and behavior Woods 2005). Cholecystokinin (CCK) stimulates the secretion of pancreatic digestive enzymes, the production and excretion of bile into the intestine, the delay of gastric emptying, and the inhibition of food intake Rehfeld 2017). Through its role as a satiety signal and regulator of energy intake, CCK is thought to act as a regulator of body weight Woods 2005).…”
Section: Discussionmentioning
confidence: 99%